Pemilihan Karyawan Terbaik Menggunakan Metode Simple Additive Weighting Berbasis Sistem Pendukung Keputusan - Kristiyanti, Dinar Ajeng; Sayoeti, Natanael (SEULANGA SYSTEM PUBLISHER, 2022)
One alternative in making effective decisions is the Decision Support System (DSS). The selection of the best employees still has weaknesses in PT. Petromitra Pacific Internusa so that it will trigger conflicts between employees. In this study, the Simple Additive Weighting (SAW) method was used to process employee data in all divisions to obtain accurate results. The SAW method is one of the methods that can assist in the decision-making process for selecting the best 100 employees by providing criteria and preference weights that can be determined according to applicable regulations such as 35% discipline criteria, 15% cooperation, 45% leadership, and honesty. 10%. This study aims to provide more accurate results and make it easier for the Personnel or HRD department to choose the best employees at PT. Petromitra Pacific Internusa. The results of this study are in the form of determining the selection of the best employees who are identified based on the results of the highest score. So that they will automatically become the best employees and will receive bonuses, as well as get a promotion.